Adopting Distributive and Compensatory Justice to Determine Optimal Tax Treatment for Corporate Donations - Younis A. Battal Saleh (CV. Pustaka Parawali, 2026)
This study aims to demonstrate how to determine the tax treatment of corporate donations in a scientifically correct manner that ensures the following: First, tax justice among donor companies. Second, justice and equality of rights among stakeholders. Third, avoiding the distortion of the thought of CSR. This study adopts the concepts of distributive and compensatory justice to determine optimal tax treatments for corporate donations. Evaluating corporate donations on the ground is essential to determine tax treatment under this approach. Based on the results of the evaluation, the following actions are taken: First, forming logical perceptions that reflect the explicit and implicit meanings of donations as they are in reality. Second, determining the type of justice (distributive or compensatory) that should be adopted as the basis for tax treatment. Using a distributive and compensatory justice approach that is based primarily on rational evaluation, this research article identified